"Systems in motion. Avantext and variants from the author lab to the critical laboratory". Chronicle of the conference, Pavia, 1-2 dicembre 2016 (Prassi Ecdotiche della Modernità Letteraria, 2017)
The conference "Systems in motion. Avantext and variants from the author lab to the critical laboratory", held in Pavia on 1th and 2nd December 2016, was born from the collaboration between the Manuscripts Center of the University of Pavia, the ITEM (Institut des Textes Manuscrits Modernes, CNRS-ENS) and the Ghisleri College, in whose spaces it took place.The busy program of the conference has intertweaved research experiences with theoretical expositions, bringing together scholars of Italian and French schools.The conference proceedings are now published in Systems in Motion, «Autografo», a. XXV, n. 57, 2017.
Keywords: avantext; variants; genetic criticism; textual criticism; author's philology